2006
DOI: 10.1152/ajpheart.00767.2005
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal intermittent hypoxia alters baroreflex function in adult rats

Abstract: Soukhova-O'Hare, Galia K., Zixi (Jack) Cheng, Andrew M. Roberts, and David Gozal. Postnatal intermittent hypoxia alters baroreflex function in adult rats. Am J Physiol Heart Circ Physiol 290: H1157-H1164, 2006. First published September 9, 2005 doi:10.1152/ajpheart.00767.2005.-Chronic perinatal intermittent hypoxia (IH) could have long-term cardiovascular effects by altering baroreflex function. To examine this hypothesis, we exposed rats (n ϭ 6/group) for postnatal days 1-30 or prenatal embryonic days 5-21 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 52 publications
1
44
1
1
Order By: Relevance
“…The observations during sleep appear to be in line with the selective impairment of baroreflex response to hypotensive agents found in untreated OSA during wakefulness [38]. Overall, the current study confirms that long-term CPAP treatment is necessary to reverse chronic autonomic dysfunction during sleep [1,4,5,8] and wakefulness [6,8,39,40], possibly in relation to recovery of cardiac vagal fibres after protracted resolution of intermittent hypoxia [41]. Thus, the autonomic dysfunction associated with severe OSA appears not to be as readily reversible as the decreased BRS in snorers [17].…”
Section: Discussionsupporting
confidence: 85%
“…The observations during sleep appear to be in line with the selective impairment of baroreflex response to hypotensive agents found in untreated OSA during wakefulness [38]. Overall, the current study confirms that long-term CPAP treatment is necessary to reverse chronic autonomic dysfunction during sleep [1,4,5,8] and wakefulness [6,8,39,40], possibly in relation to recovery of cardiac vagal fibres after protracted resolution of intermittent hypoxia [41]. Thus, the autonomic dysfunction associated with severe OSA appears not to be as readily reversible as the decreased BRS in snorers [17].…”
Section: Discussionsupporting
confidence: 85%
“…(22,23) Alternatively, the association between pre-eclampsia and SDB could be mediated by fetal hypoxia. (24)(25)(26)(27)(28)(29)(30),(31) Pre-eclampsia may cause chronic fetal hypoxia directly via maternal vascular insufficiency with subsequent reduction of fetal oxygen delivery due to placental insufficiency, or may be acting as a marker for intermittent maternal hypoxia associated with maternal SDB. The association of childhood SDB with mild but not severe pre-eclampsia is of particular interest because it is consistent with proposed differences in the biology of mild versus severe pre-eclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we showed that vagal cardiac motor neurons in the nucleus ambiguus projecting to cardiac ganglia play an important role in the baroreflex control of the HR (10 -12). More recently, we found that postnatal CIH exposures led to altered baroreflex function in adult rats, and that the associated reduction of vagal efferent axon projections to cardiac ganglia could contribute to the long-term modification in baroreflex function (46).…”
mentioning
confidence: 89%
“…In addition, we showed that vagal cardiac motor neurons in the nucleus ambiguus projecting to cardiac ganglia play an important role in the baroreflex control of the HR (10 -12). More recently, we found that postnatal CIH exposures led to altered baroreflex function in adult rats, and that the associated reduction of vagal efferent axon projections to cardiac ganglia could contribute to the long-term modification in baroreflex function (46).Although progress has occurred in the understanding of alterations in baroreceptor reflex function following intermittent hypoxia (24,29,30,42,46,47,49), very little is currently known about the structural and functional changes of sensory afferent, central and efferent components of the reflex, and their molecular underpinnings. Mice are particularly useful mammalian models that are not only susceptible to genetic manipulation but can also be used in physiological, anatomical, cellular, and molecular studies (5, 6).…”
mentioning
confidence: 99%